A method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology

Through the biocarbonated activated magnesium oxide technology, the prehydrolyzed urea solution is combined with the activated magnesium oxide curing agent, which solves the problem of dredging sludge curing with high moisture content, and achieves efficient curing and environmentally friendly and energy-saving effects.

CN115626758BActive Publication Date: 2025-03-04NANJING UNIV

Patent Information

Application Number
CN202211271891.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-18
Publication Date
2025-03-04
Estimated Expiration
2042-10-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently cure high moisture content dredging sludge, and traditional curing methods have problems with environmental protection and energy consumption.

Method used

Using biocarbonated activated magnesium oxide technology, the slurry is formed by combining the prehydrolyzed urea solution with the activated magnesium oxide curing agent to form a slurry and cure under specific conditions to achieve efficient curing of dredged sludge.

Benefits of technology

The cured samples obtained have the advantages of high strength, low permeability, strong erosion and disintegration resistance and good durability, and are environmentally friendly and energy-saving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115626758B_ABST
    Figure CN115626758B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for solidifying dredged sludge by using biological carbonization activated magnesium oxide technology, and belongs to the technical field of soil solidification. In the present invention, urease-producing bacteria are first used to prepare a pre-hydrolyzed urea solution, and then the pre-hydrolyzed urea solution and an activated magnesium oxide solidifying agent are separately and evenly mixed into dredged sludge with a certain water content according to a certain dosage, stirred to form a slurry, and the slurry is filled in a designated site or model and fully maintained. The present invention greatly reduces the construction cost and improves the feasibility and efficiency of solidification treatment of dredged sludge with high water content by introducing the technology of carbonization of urea solution pre-hydrolyzed by urease-producing microorganisms and activated magnesium oxide solidifying agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soil solidification, and more specifically, relates to a method for solidifying dredged sludge by utilizing biological carbonization active magnesium oxide technology. Background Art

[0002] During the construction and maintenance of water conservancy and water transport projects in my country, a large amount of dredged sludge is generated. According to statistics, the total amount of dredged sludge generated in my country each year can reach hundreds of millions of cubic meters. Regular dredging is essential to maintain the normal operation of water transport systems such as ocean ports, waterways and inland rivers. However, due to the natural characteristics of dredged sludge, such as high water content, high compressibility, low permeability, and even heavy metal pollution, the country has to invest huge amounts of money in the reasonable disposal of dredged sludge every year.

[0003] Traditional dredged sludge treatment mainly includes three methods: mud dumping, filling and landfilling. Although mud dumping, also known as ocean dumping, can handle large amounts of dredged sludge, it has been banned in many countries because it will cause serious pollution to the marine ecological environment. On the one hand, the filling project is restricted by the filling site. At the same time, the foundation after filling is weak, and a large amount of capital cost is often required to drain and reinforce the foundation in the later stage. The landfill method is to transport the dredged sludge to a designated site and rely on long-term self-precipitation and degradation to make it reasonably disposed of, but there is a risk of secondary pollution of the soil due to leakage from the landfill site.

[0004] The resource utilization of dredged sludge not only conforms to the green and environmentally friendly development concept, but also can reduce the country's investment cost in dredged sludge disposal to a certain extent, thereby ensuring that the dredged sludge can be effectively disposed of and achieve both ecological and economic benefits. At present, the commonly used dredged sludge solidification and resource utilization technologies at home and abroad mainly include physical dehydration, heat treatment and chemical solidification. Physical dehydration, namely natural drying and mechanical dehydration, the former occupies a large site, has a long treatment cycle, and is easily affected by weather conditions, and the latter has high investment costs and limited processing capacity; heat treatment, namely high-temperature sintering and melting, not only has requirements for the quality of dredged sludge, but also has limited processing capacity; and for the chemical solidification method, due to the high carbon emissions and high energy consumption in the production process of cement and other curing agent raw materials, and the poor solidification effect on high-water content dredged sludge, its application is also subject to certain limitations.

[0005] Therefore, in view of the above existing problems, there is an urgent need for an efficient and environmentally friendly soil solidification technology to achieve the reasonable disposal of high-water content dredged sludge. Summary of the invention

[0006] 1. Problem to be solved

[0007] In view of the technical problem that high-water-content dredged sludge solidification is difficult, the present invention provides a method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology to realize resource utilization of dredged sludge. This method not only conforms to the concept of green and environmentally friendly ecological development, but also can achieve efficient solidification treatment of large volumes of high-water-content dredged sludge, and is not restricted by construction conditions such as the site. The solidified dredged sludge can be used as building backfill such as foundation, and can also be used as anti-seepage material for construction of sites such as landfills, thereby realizing its resource utilization.

[0008] 2. Technical solution

[0009] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0010] A method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology comprises the following steps:

[0011] Preparation of S1 pre-hydrolyzed urea solution:

[0012] S1-1 adding a bacterial solution having urease activity to urea, stirring and mixing the mixture to form a urea solution;

[0013] S1-2 pre-hydrolyzing the urea solution for a specific time to allow the urease-producing bacteria in the bacterial solution to hydrolyze the urea to obtain a pre-hydrolyzed urea solution; preferably, the pre-hydrolysis of the urea solution is performed under conditions avoiding direct sunlight and / or in a closed state to prevent the volatilization of the solvent;

[0014] S2: adding the pre-hydrolyzed urea solution and the active magnesium oxide curing agent prepared in step S1-2 to the dredged sludge separately, and stirring to form a slurry;

[0015] S3 slurry filling and curing: the slurry in step S2 is filled in the model and cured for a certain period of time under specific temperature and humidity conditions.

[0016] Preferably, the concentration c of the urea solution in step S1-1 is 0 mol / L <c≤4mol / L。

[0017] Preferably, the urea utilization rate θ of the pre-hydrolyzed urea solution in step S1-2 is preferably greater than 5%. The urea utilization rate θ can be obtained by testing the acid washing exhaust method, and the specific process is as follows:

[0018] The entire test process is carried out under normal temperature and pressure (temperature is 25℃, atmospheric pressure is 101kPa). Figure 1 As shown, the reference steps of the test process are as follows:

[0019] ① Check the air tightness of the device;

[0020] ② Pour 10 ml of pre-hydrolyzed urea solution into conical flask A and seal it with a rubber stopper (such as Figure 1 ) and check the air tightness of the device again;

[0021] ③ Slowly inject 80 ml of 1 mol / L hydrochloric acid solution into conical flask A through a separatory funnel, and then keep the piston of the separatory funnel closed;

[0022] ④ Start the magnetic stirrer; when the water level in the wide-mouth bottle stops dropping or when no water flows into the conical flask B, turn off the magnetic stirrer;

[0023] ⑤At this time, the difference between the volume of water flowing into conical flask B and the volume of hydrochloric acid solution injected into conical flask A (80ml) is recorded as V t .

[0024] The calculation formula of urea utilization rate θ is as follows:

[0025]

[0026] Wherein, θ is the urea utilization rate of the pre-hydrolyzed urea solution, %; V t is the difference between the volume of water flowing into conical flask B and the volume of hydrochloric acid solution injected into conical flask A, L; c is the concentration of urea solution, mol / L.

[0027] Preferably, the pre-hydrolysis time in step S1-2 is not less than 2 hours to ensure that the urea utilization rate θ is greater than 5%.

[0028] Preferably, the moisture content of the dredged sludge in step S2 is greater than or equal to 80%.

[0029] Preferably, the addition amounts of the pre-hydrolyzed urea solution and the active magnesium oxide curing agent in step S2 satisfy the following relationship:

[0030]

[0031]

[0032] Where x is the dosage of the pre-hydrolyzed urea solution used, %; m u is the mass of the pre-hydrolyzed urea solution used, kg; y is the dosage of the active magnesium oxide curing agent used, %; m RMC is the mass of the active magnesium oxide curing agent used, kg; m s is the mass of solid particles in the dredged sludge, kg.

[0033] Preferably, the dosage of the pre-hydrolyzed urea solution in step S2 is 10% to 30%, the dosage of the active magnesium oxide curing agent is not less than 5%, and the content of active magnesium oxide in the active magnesium oxide curing agent should be not less than 10%.

[0034] Preferably, the bacterial liquid having urease activity is Sporosarcina pasteurianum, and the formula of the liquid culture medium used for the bacterial liquid is: 10 g / L ammonium sulfate, 20 g / L yeast extract and 15.73 g / L Tris base; after the bacterial liquid is inoculated into the liquid culture medium that has been fully sterilized by high temperature at a volume fraction of 1% to 3%, it is cultured in a constant temperature shaking incubator at 30°C and 200 rpm for 24 hours or more.

[0035] Preferably, the initial temperature of the bacterial solution with urease activity is 20°C to 35°C, and the urease activity of the bacterial solution tested by a conductivity meter is not less than 0.1 mS·cm -1 / 5min, according to the OD tested by the microplate reader 600 The value should not be less than 0.2.

[0036] Preferably, in step S3, the curing temperature is 20° C. to 35° C., and the relative humidity is above 60%.

[0037] Specifically, the present invention provides a method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology, comprising the following steps:

[0038] Step 1: Preparation of prehydrolyzed urea solution

[0039] First, a bacterial liquid with a certain urease activity of volume V is added to solid urea of ​​mass m, and the mixture is stirred and mixed to prepare a urea solution with a urea concentration of c; secondly, the prepared urea solution is stored for T hours in a sealed or unsealed state under the condition of avoiding direct sunlight to give full play to the hydrolysis effect of urease-producing bacteria in the bacterial liquid on urea;

[0040] The bacterial liquid with a certain urease activity is pasteurian spore Sarcina, and the formula of the liquid culture medium used for the bacterial liquid is: 10g / L ammonium sulfate, 20g / L yeast extract and 15.73g / L Tris base. After the bacterial liquid is inoculated into the liquid culture medium that has been fully sterilized at high temperature at a volume fraction of 1% to 3%, it is cultured in a constant temperature shaking incubator at 30°C and 200 rpm for 24 hours or more;

[0041] The initial temperature of the bacterial solution is 20°C to 35°C, and the urease activity of the bacterial solution tested by a conductivity meter is not less than 0.1 mS·cm -1 / 5min, according to the OD tested by the microplate reader 600 The value is not less than 0.2;

[0042] The urea concentration c of the configured urea solution is optimally in the range of 0 mol / L < c ≤ 4 mol / L to ensure that the urease activity expression of the bacterial solution is not inhibited by high-concentration urea. The calculation formula for the urea concentration in this step is as follows:

[0043]

[0044] Where c is the urea concentration, mol / L; n is the molar mass of the solid urea used, mol; m is the mass of the solid urea used, g; M is the relative molecular mass of urea, 60 g / mol; V is the volume of the configured urea solution (the mixed solution of the bacterial solution and solid urea), L.

[0045] The closed storage time T of the configured urea solution should be not less than 2 hours. The solution after T hours of closed storage is called: pre-hydrolyzed urea solution.

[0046] Step Two: Incorporation of curing agent

[0047] The curing agent includes two parts: reactive magnesium oxide curing agent and the pre-hydrolyzed urea solution described in Step One.

[0048] First, pour a certain dosage of the pre-hydrolyzed urea solution into the dredged sludge with a water content of w, and use a mechanical stirring device such as a concrete mixer to stir it充分. Then, pour a certain dosage of the reactive magnesium oxide curing agent into the stirring device in the same way and stir it充分 with the former to mix evenly, forming a slurry; or pour a certain dosage of the reactive magnesium oxide curing agent into the dredged sludge with a water content of w, and use a mechanical stirring device such as a concrete mixer to stir it充分. Then, pour a certain dosage of the pre-hydrolyzed urea solution into the stirring device in the same way and stir it充分 with the former to mix evenly, forming a slurry.

[0049] According to YB / T 4019-2020 "Determination Method for Chemical Activity of Light-Burned Magnesium Oxide", the content of reactive magnesium oxide in the reactive magnesium oxide curing agent should be not less than 10%.

[0050] Preferably, the water content w of the dredged sludge that can be cured by the method of the present invention is not limited, and different curing effects on dredged sludge with different water contents can be achieved by adjusting the proportion of the curing agent used. The expression of the water content w is as follows:

[0051]

[0052] Where w is the water content of the dredged sludge, %; m w is the mass of water in the dredged sludge, kg; m s is the mass of solid particles in the dredged sludge, kg.

[0053] Preferably, the dosage of the pre-hydrolyzed urea solution is 10% to 30%, and the dosage of the active magnesium oxide curing agent is not less than 5%. The specific calculation expression is as follows:

[0054]

[0055]

[0056] Where x is the dosage of the pre-hydrolyzed urea solution used, %; m u is the mass of the pre-hydrolyzed urea solution used, kg; y is the dosage of the active magnesium oxide curing agent used, %; m RMC is the mass of the active magnesium oxide curing agent used, kg; m s is the mass of solid particles in the dredged sludge, kg.

[0057] Step 3: Slurry filling and curing

[0058] The slurry formed by adding the curing agent in step 2 is filled in a pre-planned site or a prefabricated model, and cured for more than 48 hours under environmental conditions of a temperature of 20° C. to 35° C. and a relative humidity of more than 60%;

[0059] It should be noted that the curing temperature should be between 20°C and 35°C and the relative humidity of the curing environment should be 60% or above. Too high or too low temperature and humidity conditions are also acceptable, but may result in poor solidification of the dredged sludge. The curing time should be higher than 48 hours to achieve a higher solidification effect.

[0060] 3. Beneficial effects

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] (1) The present invention provides a method for solidifying dredged sludge by using biocarbonized activated magnesium oxide technology. In the method, urea is placed in a bacterial solution with urease activity for pre-hydrolysis for a specific time so that the urease-producing bacteria in the bacterial solution hydrolyze the urea to obtain a pre-hydrolyzed urea solution. The prepared pre-hydrolyzed urea solution and an activated magnesium oxide solidifying agent are separately added to dredged sludge with a certain moisture content, stirred to form a slurry, and cured to obtain a solidified sample. The solidified sample has the advantages of high strength, low permeability, strong erosion resistance and anti-disintegration ability, and good durability.

[0063] (2) In the method of the present invention, it is preferred that the pre-hydrolyzed urea solution can produce a large amount of carbonate ions, thereby providing sufficient material sources for the carbonization reaction of the active magnesium oxide curing agent; for example, a urea solution with a urea concentration of 2 mol / L can achieve a urea utilization rate of more than 50% after 24 hours of pre-hydrolysis. The pre-hydrolyzed urea solution contains a large amount of carbonate ions required for the carbonization reaction of the active magnesium oxide curing agent, and has a better curing effect on high-water-content dredged sludge than the solution without pre-hydrolysis (i.e., the pre-hydrolysis time is 0 hours);

[0064] (3) The present invention has obvious advantages in solidifying high-water content dredged sludge (water content up to 80% and above); it overcomes the shortcomings of the existing soil solidification technology (such as cement curing agent) that the solidification effect is poor, and the solidified dredged sludge is not prone to shrinkage and cracking, and has good durability;

[0065] (4) The present invention provides a method for solidifying dredged sludge by using biocarbonized activated magnesium oxide technology, which utilizes urease-producing bacteria widely distributed in natural soil to catalyze and promote the hydrolysis of urea to produce carbonate ions, and then reacts with the hydration products of activated magnesium oxide to undergo carbonization reaction. The dredged sludge can be efficiently solidified by the bonding and filling effects of activated magnesium oxide water and carbonization products. The urease-producing bacteria used are widely distributed in natural soil and will not pollute the ecological environment. The calcination production temperature of the activated magnesium oxide solidifying agent used (about 750°C) is lower than the calcination production temperature of traditional cement materials (about 1450°C), which can reduce the energy consumption and carbon emissions caused by the production of raw materials. In addition, activated magnesium oxide also has the potential to absorb and store CO2.

[0066] (5) Compared with the existing soil solidification technology, the biocarbonized activated magnesium oxide soil solidification technology used in the present invention can achieve efficient solidification of soil including dredged sludge in a shorter time, and can obtain faster and higher early strength. Generally speaking, stable strength improvement and solidification effect can be obtained after about 48 hours;

[0067] (6) The present invention can meet the needs of treating large amounts of dredged sludge, is not easily restricted by construction sites, construction equipment, and other external environmental conditions, and has simple construction operations and low initial investment costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 This is a schematic diagram of the pickling exhaust method test device.

[0069] Figure 2 This is a schematic diagram of the actual state of dredged sludge with a moisture content of 80% before and after solidification in Example 1.

[0070] Figure 3The graph is a relationship curve between the axial stress and the axial strain of the sample in the unconfined compressive strength test after solidification of the dredged sludge with a moisture content of 80% in Example 1.

[0071] Figure 4 This is a curve diagram showing the relationship between the axial stress and axial strain of the sample in the unconfined compressive strength test after the dredged sludge with a moisture content of 80% in Comparative Example 2 was solidified with silicate cement (42.5#).

[0072] Figure 5 The graph is a relationship curve between the axial stress and the axial strain of the sample in the unconfined compressive strength test after solidification of the dredged sludge with a moisture content of 120% in Example 2.

[0073] Figure 6 The graph is a relationship curve between the axial stress and the axial strain of the sample in the unconfined compressive strength test after solidification of the dredged sludge with a moisture content of 80% (pre-hydrolysis time is 12 hours) in Example 3.

[0074] Figure 7 The graph is a relationship curve between the axial stress and the axial strain of the sample in the unconfined compressive strength test after solidification of the dredged sludge with a moisture content of 80% in Example 4 (the dosage of the pre-hydrolyzed urea solution is 10%).

[0075] Figure 8 The graph is a relationship curve between the axial stress and the axial strain of the sample in the unconfined compressive strength test after solidification of the dredged sludge with a moisture content of 80% (curing time is 24 hours) in Example 5. DETAILED DESCRIPTION

[0076] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0077] In the examples, if specific conditions are not specified, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are conventional products that can be purchased commercially. As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. Those skilled in the art can easily determine the degree of flexibility of a specific variable.

[0078] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values ​​or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values ​​and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.

[0079] Any steps recited in any method or process claim may be performed in any order and are not limited to the order presented in the claims. Method+function or step+function limitations are adopted only if all of the following conditions are present in a particular claim limitation: a) explicitly recite "a method for..." or "a step for..."; b) explicitly recite the corresponding function. The structure, material, or action that supports the method+function is explicitly recited in the description herein. Therefore, the scope of the present invention should be determined solely by the appended claims and their legal equivalents, rather than by the description and examples given herein.

[0080] The present invention is further described below in conjunction with specific embodiments.

[0081] Example 1

[0082] This embodiment uses biocarbonized activated magnesium oxide technology to solidify dredged sludge with a moisture content of 80%. The specific steps are as follows:

[0083] 1) Preparation of pre-hydrolyzed urea solution: Weigh a certain mass of solid urea and add a certain volume of urease with an activity of 0.37 mS·cm -1 / 5min、OD 600 The urea solution was sealed and stored at a temperature of 25° C. and a relative humidity of 80% for 24 hours.

[0084] 2) Addition of curing agent: Take a certain amount of dredged sludge with a moisture content of 80% (flowing state, no strength), first add a pre-hydrolyzed urea solution with a dosage (x) of 20%, and stir it evenly with a mechanical stirring equipment. Then, add an active magnesium oxide curing agent with a dosage (y) of 15% (produced by Tianjin Zhiyuan Chemical Reagent Co., Ltd., batch number 20200320), mix it again, stir evenly, and form a slurry.

[0085] 3) Preparation and filling of standard cylindrical specimens: Fill the above slurry into a cylindrical mold with a diameter of 50 mm and a height of 100 mm in multiple times until the mold is full. During the filling process, the mold needs to be shaken several times to avoid the formation of closed bubbles in the slurry, which will affect the integrity of the specimen.

[0086] 4) Curing: Place the standard cylindrical specimen in an environmental chamber at a temperature of 30°C and a relative humidity of 95% for 7 days.

[0087] After curing, the specimens were demoulded. Figure 2 Schematic diagram of dredged sludge with a moisture content of 80% before and after solidification.

[0088] The unconfined compressive strength (UCS) test was carried out in accordance with DL / T 5355-2006 "Geotechnical Test Procedures for Hydropower and Water Conservancy Projects". The axial pressure loading rate during the test was 1mm / min. The relationship curve between the axial stress and axial strain of the sample after the test is as follows: Figure 3 shown.

[0089] The test results show that: Figure 3 It can be seen that the dredged sludge with a moisture content of 80% has a significant strength improvement after being solidified by biocarbonized activated magnesium oxide technology, and its unconfined compressive strength is about 1096.41 kPa. The dredged sludge with a moisture content of 80% that has not been solidified is initially in a flowing state, and its unconfined compressive strength is 0. The significant improvement in the unconfined compressive strength of the sample (from 0 kPa to 1096.41 kPa) is mainly attributed to the cementation and filling effect of the active magnesium oxide carbonization product (hydrated magnesium carbonate) inside the sample on the dredged sludge.

[0090] Comparative Example 1

[0091] In this comparative example, the prehydrolysis time of the urea solution is 0 h (without prehydrolysis), and other aspects are exactly the same as those in Example 1.

[0092] After curing, the sample did not obtain obvious curing effect, and the sample did not show mechanical strength, which was in sharp contrast to the cured sample in Example 1, fully demonstrating the advantages of the pre-hydrolyzed urea solution in the present invention.

[0093] Comparative Example 2

[0094] In this comparative example, silicate cement (labeled as 42.5#) was used to solidify dredged sludge with a moisture content of 80%. The specific steps are as follows:

[0095] 1) Addition of curing agent: Take a certain amount of dredged sludge with a moisture content of 80%, add 15% (the calculation method of the dosage is the same as that of the active magnesium oxide curing agent) of silicate cement to it, and use mechanical stirring equipment to fully stir it to form a slurry.

[0096] 2) Preparation and filling of standard cylindrical specimen: same as in Example 1.

[0097] 3) Curing: The curing conditions are the same as those in Example 1, and the curing time includes 7 days (7d), 14 days (14d) and 28 days (28d).

[0098] The unconfined compressive strength (UCS) test was carried out in accordance with DL / T 5355-2006 "Geotechnical Test Procedures for Hydropower and Water Conservancy Projects". The axial pressure loading rate during the test was 1mm / min. The relationship curve between the axial stress and axial strain of the sample after the test is as follows: Figure 4 shown.

[0099] The test results show that when the dosage of cement is the same as that of the active magnesium oxide curing agent in Example 1 of the present invention, after 7 days of curing, the unconfined compressive strength of the cement-cured sample is about 190.07 kPa, which is much lower than the strength (1096.41 kPa) of the sample cured by the present invention in Example 1; even after the cement-cured sample is cured for 14 days or 28 days, its unconfined compressive strength is only 344.71 kPa and 400.55 kPa, respectively, which is also much lower than the strength (1096.41 kPa) of the sample cured by the present invention in Example 1. The unconfined compressive strength of the sample cured by the present invention after 7 days of curing is about 5.77 times, 3.18 times and 2.74 times the unconfined compressive strength of the cement-cured sample after 7 days, 14 days and 28 days of curing, respectively. This fully reflects the advantages of the present invention in curing high-water content dredged sludge, that is, the present invention has a faster and more efficient curing effect for high-water content dredged sludge.

[0100] Example 2

[0101] In this embodiment, the moisture content of the dredged sludge is 120%, and other aspects are exactly the same as those in Embodiment 1.

[0102] The test results of the unconfined compressive strength test of the sample in this embodiment after curing and demoulding are as follows: Figure 5 shown.

[0103] The test results show that when the moisture content of the solidified dredged sludge is 120%, the unconfined compressive strength of the solidified sample using the present invention can reach about 272.76 kPa, and still has a certain solidification effect. Compared with the unconfined compressive strength (1096.41 kPa) of the dredged sludge with a moisture content of 80% in Example 1, the solidification effect is significantly worse than that of the solidified sample in Example 1. This shows that the moisture content of the dredged sludge significantly affects the solidification effect. However, in the present invention, the solidification effect of the sample can be further significantly enhanced by increasing the dosage of the curing agent.

[0104] Example 3

[0105] In this embodiment, the pre-hydrolysis time of the urea solution is 12 hours, and other aspects are exactly the same as those in Embodiment 1.

[0106] The test results of the unconfined compressive strength test of the sample in this embodiment after curing and demoulding are as follows: Figure 6 shown.

[0107] The test results show that when the pre-hydrolysis time is 12h, the unconfined compressive strength of the sample cured by the present invention is about 851.57kPa; compared with the unconfined compressive strength (1096.41kPa) of the cured sample with a pre-hydrolysis time of 24h in Example 1, the curing effect is worse than that of the cured sample in Example 1; compared with the cement cured sample (400.55kPa) cured for 28 days in Comparative Example 2, the curing effect is still significantly better than that of the cement cured sample. This shows that the pre-hydrolysis time of the urea solution has a significant effect on the curing effect of the dredged sludge sample, and the curing effect can be improved by increasing the pre-hydrolysis time; at the same time, it further reflects the curing advantage of the present invention over traditional cement.

[0108] Example 4

[0109] In this embodiment, the dosage of the pre-hydrolyzed urea solution is 10%, and other aspects are exactly the same as those in Embodiment 1.

[0110] The test results of the unconfined compressive strength test of the sample in this embodiment after curing and demoulding are as follows: Figure 7 shown.

[0111] The test results show that when the dosage of the prehydrolyzed urea solution is 10%, the unconfined compressive strength of the sample cured by the present invention is about 356.52 kPa; compared with the unconfined compressive strength (1096.41 kPa) of the cured sample with a dosage of 20% of the prehydrolyzed urea solution in Example 1, the curing effect is significantly worse than that of the cured sample in Example 1; this shows that the dosage of the prehydrolyzed urea solution has a significant effect on the curing effect of the dredged sludge sample, and the curing effect can be significantly improved by increasing the dosage of the prehydrolyzed urea solution within an appropriate range.

[0112] Example 5

[0113] In this embodiment, the curing time of the cured sample is 1 day (24 hours), and other aspects are exactly the same as those in Example 1.

[0114] The test results of the unconfined compressive strength test of the sample in this embodiment after curing and demoulding are as follows: Figure 8 shown.

[0115] The test results show that when the curing time of the cured sample is 24h, the unconfined compressive strength of the cured sample using the present invention is about 824.24kPa; compared with the unconfined compressive strength (1096.41kPa) of the cured sample with a curing time of 7 days in Example 1, the curing effect is worse than that of the cured sample in Example 1; this shows that the curing time of the cured sample also affects the curing effect of the dredged sludge sample, and the curing effect can be improved by extending the curing time, but generally after 48 hours of curing, the effect of the curing time on the curing effect can be basically ignored.

[0116] It should be pointed out that although exemplary embodiments of the present invention have been described herein, the present invention is not limited to the above five specific embodiments, but includes any and all embodiments formed by any adaptive changes such as addition, reduction, modification, replacement or combination made by those skilled in the art to the disclosed technical features according to the previous detailed description. The limitations in the claims can be interpreted broadly according to the language used in the claims, and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. Any steps listed in any method or process claim can be performed in any order and are not limited to the order proposed in the claim. Therefore, the scope of the present invention should be determined only by the attached claims and their legal equivalents, rather than by the description and examples given above. Therefore, if a person of ordinary skill in the art is inspired by it, without departing from the purpose of the invention, a structural mode and embodiment similar to the technical solution without creativity should belong to the scope of protection of the present invention.

Claims

1. A method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology, characterized in that: The steps include: S1 Preparation of pre-hydrolyzed urea solution: S1-1 adding a bacterial solution having urease activity to urea, stirring and mixing the mixture to form a urea solution; the concentration c of the urea solution is 0 mol / L< c ≤4 mol / L; S1-2 pre-hydrolyzing the urea solution for no less than 2 hours, so that the urease-producing bacteria in the bacterial solution hydrolyze the urea to obtain a pre-hydrolyzed urea solution; S2: adding the pre-hydrolyzed urea solution and the active magnesium oxide curing agent prepared in step S1-2 to the dredged sludge separately, and stirring to form a slurry; the water content of the dredged sludge is greater than or equal to 80%; S3 Slurry filling and curing: the slurry in step S2 is filled in a model, and cured for more than 48 hours under environmental conditions of a temperature of 20° C. to 35° C. and a relative humidity of more than 60% to obtain a solidified sample.

2. The method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology according to claim 1, characterized in that: The urea utilization rate of the pre-hydrolyzed urea solution in step S1-2 Greater than 5%.

3. The method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology according to claim 1, characterized in that: The addition amounts of the pre-hydrolyzed urea solution and the active magnesium oxide curing agent in step S2 satisfy the following relationship: Wherein, x is the dosage of pre-hydrolyzed urea solution used, %; m u is the mass of the pre-hydrolyzed urea solution used, kg; y is the dosage of the active magnesium oxide curing agent used, %; m RMC is the mass of the active magnesium oxide curing agent used, kg; m s is the mass of solid particles in the dredged sludge, kg.

4. The method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology according to claim 3, characterized in that: The dosage of the pre-hydrolyzed urea solution in step S2 is 10% to 30%, the dosage of the active magnesium oxide curing agent is not less than 5%, and the content of active magnesium oxide in the active magnesium oxide curing agent should be not less than 10%.

5. The method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology according to claim 1, characterized in that: The bacterial liquid with urease activity is pasteurian spore Sarcina, and the formula of the liquid culture medium used for the bacterial liquid is: 10 g / L ammonium sulfate, 20 g / L yeast extract and 15.73 g / L Tris base; after the bacterial liquid is inoculated into the liquid culture medium that has been fully sterilized by high temperature at a volume fraction of 1% to 3%, it is cultured in a constant temperature shaking incubator at 30°C and 200 rpm for more than 24 hours.

6. The method for solidifying dredged sludge using biocarbonized activated magnesium oxide technology according to any one of claims 1 to 5, characterized in that: The initial temperature of the bacterial solution with urease activity is 20°C to 35°C, and the urease activity of the bacterial solution tested by a conductivity meter is not less than 0.1 mS·cm -1 / 5min, according to the OD tested by the microplate reader 600 The value should not be less than 0.2.

Citation Information

Patent Citations

  • Microbial solidification method for dredged sludge

    CN107352768A

Cited By

  • Roadbed filling construction method for internal and external source carbonization reinforcement

    CN120844418A

  • Construction method for reinforcing collapsible loess foundation based on grouting carbonization-vibration densification cooperation

    CN122013759A